Social media testing of described activities in the manual “Art-based activities to promote local and rural cultural heritage“ - Kabasinskaite Kotryna; Liorentiene Kristina; Lefebvre Augustin; Nyikos Julia; Mutta Maarit; Merijärvi Soila; Lucantoni Grazia; Moncada Maria; Lucantoni Silvia (Dadau, 2025)
The implementation of Erasmus+ CORDIALIS project activities involved writing the manual which presented 15 different participatory social media activities with instructions on how to adapt it to artisans work in real life. Each partner country presented examples which can serve as a guide and encourage better uptake of market opportunities, increased market penetration with less individual effort, controlled seasonality, increased competitiveness, increased credibility and better craftsmen business image in the future. Also, more complex product, unique experiences can help to attract more tourists which ensures the smooth running of artisan’s business.
CORDIALIS partners aimed to find out how these described examples actually work in real life. Finnish, Italian and Lithuanian partners selected one or more activities and tested them on their social media accounts in their local languages. In this document information provided about how the partners did the testing in and what observations they found. Five activities in total were tested.
The main manual “Art-based activities to promote local and rural cultural heritage” (2023) with all 15 activities is available through an online resource centre created by CORDIALIS (https://www.cordialiserasmus.eu).